Bridging gaps and shaping futures: digital informal learning and the construction of possible selves in Chinese higher education - Liu, Zihao; Zhang, Jian; Liu, Chixiaofei; He, Qingwei (Frontiers in Education, 2025)
IntroductionDigital informal learning (DIL) has become increasingly important in higher education, providing a flexible complement to traditional instruction and supporting students’ academic and personal development. This study explores how Chinese university students engage with DIL through the lens of ‘possible selves’, examining how their envisioned identities motivate their informal learning behaviours.MethodsA mixed-methods design was employed at a Chinese university, combining quantitative survey data from 514 undergraduate students with qualitative data from in-depth interviews with 18 participants. The survey assessed students’ conceptual understanding, attitudes, and usage frequency of DIL, while interviews provided deeper insights into their motivations and experiences.ResultsSurvey findings indicated that although students had limited conceptual knowledge of DIL, the majority recognised its significance and routinely integrated it into daily learning practices. Interview data further revealed that students predominantly utilised DIL to compensate for formal education shortcomings, such as limited classroom time, outdated materials, and insufficient teaching quality. Additionally, students’ engagement with DIL was strongly influenced by their aspirations (ideal academic selves) and their fears of academic failure (feared selves), shaping DIL use as both a remedial strategy and a proactive measure for self-improvement.DiscussionThe findings underscore the dual role of DIL in addressing formal curriculum gaps and fostering self-directed personal growth, while also highlighting potential risks such as fragmented knowledge acquisition and information overload. The study extends the ‘possible selves’ theoretical framework into the digital learning context and offers practical implications for curriculum development, teacher professional development, and digital literacy initiatives. Ultimately, this research advances the understanding of leveraging digital learning innovations to create more responsive and equitable educational environments.